2003
DOI: 10.1590/s0100-39842003000400007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do ângulo ano-retal por meio de defecograma em voluntárias assintomáticas nulíparas e multíparas

Abstract: Santos JEM et al. Radiol Bras 2003;36(4):219224 219 INTRODUÇÃOEste trabalho objetivou preencher uma lacuna na literatura nacional a respeito do exame de defecograma e comparar os achados radiográficos obtidos entre nulíparas e multíparas assintomáticas, assunto pouco explorado na literatura mundial.As primeiras tentativas de estudo dos mecanismos da defecação tiveram início na década de 60(1-3 OBJETIVO: Fizemos um protocolo para compararmos as medidas dos ângulos ano-retais em três situações diferentes, em vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…That indicates, indirectly, that the methods employed correctly indicated the need for the examinations; that is, that the examinations were performed in individuals who were truly ill. Anterior rectocele was the diagnosis that was most prevalent in all of the patient subgroups, and we found that the changes of the pelvic floor were more related to multiple associated disorders, parity, and prior disease than to the age of the patient, as was also observed in the study conducted by Santos et al (17) .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…That indicates, indirectly, that the methods employed correctly indicated the need for the examinations; that is, that the examinations were performed in individuals who were truly ill. Anterior rectocele was the diagnosis that was most prevalent in all of the patient subgroups, and we found that the changes of the pelvic floor were more related to multiple associated disorders, parity, and prior disease than to the age of the patient, as was also observed in the study conducted by Santos et al (17) .…”
Section: Discussionsupporting
confidence: 84%
“…All of these diagnoses have a direct effect on patient quality of life. Unlike the physical examination, defecography allows early diagnosis of multiple dysfunctions of the pelvic floor, which completely changes the surgical approach (17) .…”
Section: Discussionmentioning
confidence: 99%